COVID-19 Pandemic Preparedness in Egypt's Teaching Hospitals: A Needs Assessment Study - Abd El Ghaffar, Muhammad Mostafa; Salem, Marwa Rashad; Al Soda, Mohamed Fawzy; Abd El Razik, Madiha Said; Tahoon, MarwAli Hassab; Tahoon, Mohamed Fathy; Eysa, Basem; Hegazy, Abd Elfattah Elsayed; Eleraky, Abdelkarem Emam; Eltayar, Ayman A.; Eldarandly, Wael Mahmoud Hossam El Din; Omran, Dalia (Frontiers in Public Health, 2022)
Introduction Regular collection and monitoring of data describing the dynamics of the utilization of healthcare services, especially in teaching hospitals (TH), which provide model quality medical services, are critical for COVID-19 pandemic preparedness. Methods The researchers analyzed data and information derived from service statistics reports from June 1st to July 15th, 2020 in terms of hospital resources, as well as utilization patterns of beds, ICU, and ventilators, for 11 screening hospitals affiliated with the General Organization of Teaching Hospitals and institutes in Egypt assigned by the Ministry of Health and Population to provide medical care for COVID-19 patients. Hospital indicators in terms of COVID-19 screening services, as well as utilization patterns of inpatient beds, ICU beds, and ventilators were computed. Results A total of 78,869 non-medical personnel and 2,176 medical personnel were presented with COVID-19 triage symptoms. Investigations conducted in the targeted 11 hospitals delineated that 22.2% of non-medical personnel and 27.9% of medical personnel were COVID-19 PCR-confirmed cases. The inpatient bed occupancy rate was 70% for non-medical patients and 67% for medical staff patients. For ICU, the bed occupancy rate was 92 % for non-medical patients and 88% for medical patients. Among the confirmed cases, 38% of medical patients utilized a ventilator vs. 36% of medical personnel cases. Hospital ranking according to utilization pattern among non-medical personnel, Hospital H ranked first in terms of the high load of screening services. Hospital C ranked first regarding the number of confirmed cases, whereas Hospital D ranked first for high ICU utilization among all teaching hospital ICU cases. With respect to medical personnel, Hospital G ranked first for the high load of screening services for the total studied cases. Hospital G ranked first for the number of confirmed cases. Hospital B ranked first regarding high ICU utilization among all teaching hospital ICU cases. Conclusion Teaching hospitals have demonstrated preparedness for the COVID-19 pandemic by maintaining an inpatient bed occupancy rate of 70% or less and ventilator utilization at <40% of confirmed cases. However, the ICU bed occupancy rate was more than 90% indicating a shortage of resources. In addition, there is variance across hospitals regarding caseload for resource reallocation decisions.